The effect of water storage on nanoindentation creep of various CAD-CAM composite blocks - Rasha A. Alamoush; Nesreen A. Salim; Alaaeldin Elraggal; Julian D. Satterthwaite; Nikolaos Silikas (BMC, 2023)
Abstract Background To study the effect of water storage (3 months) on the creep deformation of various CAD-CAM composite structures at the nanoscale and compare it to that at the macroscale. Methods Seven CAD-CAM blocks were investigated: five resin-composite blocks (RCB), one polymer-infiltrated ceramic network (PICN) block, and one ceramic-filled polyetheretherketone (PEEK) block. Specimens of each material (n = 6) were separated into two groups (n = 3) according to their storage conditions (24 h dry storage at 23˚C and 3 months storage in 37˚C distilled water). Nano-indentation creep measurements were undertaken (creep depth measured in µm) using a nanoindenter (Nanovea) equipped with Berkovich three-sided pyramidal diamond tip. The machine was set for the chosen parameters: a load of 20 gf, a pause of 20 s, and the material type. Thirty indentations on 3 samples were made for each material for each test. Data were analysed using two-way ANOVA followed by one-way ANOVA and Bonferroni post hoc tests and independent t-test (< 0.05) for comparisons between the materials. Results The nanoindentation creep depth after 24 h storage ranged from 0.09 to 0.33 μm and increased after 3 months storage in distilled water to between 0.28 and 3.46 μm. There was a statistically significant difference in nanoindentation creep behaviour between the two storage conditions for each investigated material (independent t-test) and between all materials (Bonferroni post hoc). There was a non-significant negative correlation between nanoindentation creep (µm) and filler weight% at 24 h dry storage but a significant correlation at 3 months of water storage. A further non-significant positive correlation between nanoindentation creep (µm) and bulk compressive creep (%) was found. Conclusion The PICN material showed superior dimensional stability in terms of nanoindentation creep depth in both storage conditions. Other composite blocks showed comparable performance at 24 h dry condition, but an increased nanoindentation creep upon water storage.